The effect of mindfulness-based counseling on the childbirth experience of primiparous women: a randomized controlled clinical trial - Bahare Sharegi Oskoui; Esmat Mehrabi; Roghaiyeh Nourizadeh; Khalil Esmaeilpour (BMC, 2023)
Abstract Introduction Unpleasant childbirth experience is considered as one of the important factors for cesarean preference. Limited studies have been investigated the impact of psycho-based interventions on the childbirth experience and the most effective counseling approach to promote a pleasant childbirth experience has not been clearly identified. Objective The present study aimed to evaluate the impact of mindfulness-based counseling on the childbirth experience of primiparous women. Methods and materials This randomized controlled clinical trial was conducted on 64 primiparous with gestational age of 32 to 34 weeks referred to the perinatology clinic of Al-Zahra and Taleghani educational-treatment hospital, affiliated to Tabriz University of Medical sciences, Iran. Participants were randomly assigned into the intervention and control groups. The intervention group received eight mindfulness-based counseling sessions. The intensity of childbirth pain with VAS (Visual Analog Scale) in the active phase of labor at 8 cm dilatation and the childbirth experience questionnaire were completed by interview after childbirth. Independent t-test and ANCOVA were used to compare the outcomes between the two groups. Results After controlling the effect of confounding variables, the mean score of childbirth experience in the intervention group was significantly higher than that in control group [Mean Difference (MD): 1.79, 95% CI: 2.52 to 1.07, P < 0.01]. The mean score of labor pain in the intervention group was significantly lower than that in the control group after controlling the effect of baseline score and confounding variables [MD: -2.21, 95% CL: -3.35 to -1.10, P < 0.001]. Conclusion The findings indicated that providing mindfulness-based counseling improves the childbirth experience and reduces labor pain during childbirth. However, further randomized clinical trials are needed before making a definitive conclusion. Trial registration Iranian Registry of Clinical Trials (IRCT): IRCT20171007036615N9. Date of registration: 16/03/2022, 25/12/1400.